The Role of Islamic Religious Education Teachers in Developing Students’ Discipline Character: A Qualitative Study - Fauzannur, Fauzannur (Newinera Publisher, 2025)
Teachers play an important role in the formation of students' disciplined character, but there are still some teachers who cannot provide good examples in terms of discipline. This study aims to identify the approach to the formation of disciplined character and analyze the application of disciplined character carried out by Islamic Religious Education (PAI) teachers at SMA PGRI 2 Sampit, as well as analyzing the transformation of student behavior as a result of the process. The research method used is qualitative with a naturalistic approach, where data is obtained through observation, in-depth interviews, and documentation with research subjects, namely PAI teachers, and informants from the principal, BK teachers, student affairs teachers, homeroom teachers, and students. Data validation uses triangulation techniques and source triangulation, and data analysis uses the steps of reduction, data presentation, drawing conclusions and verification. The results of the study indicate that the approach to the process of forming disciplined character is carried out through: (1) habituation of worship, which instills spiritual and moral discipline; (2) teacher role models in consistent attitudes, words, and actions; and (3) spiritual strengthening through intensive religious learning and guidance at SMA PGRI 2 Sampit. Meanwhile, the application of discipline as a character builder in schools is reflected in Islamic communication, fairness and social empathy, and role models in daily interactions. The transformation of student behavior is evident in increased discipline, honesty, responsibility, independence, and self-control. This finding aligns with Al-Ghazali's view of moral education as a process of purifying the soul (tazkiyatun nafs) and cultivating good behavior, while also strengthening the relevance of modern character education theory. This study confirms that Islamic Religious Education teachers have a strategic role in building disciplined character at SMA PGRI 2 Sampit